Bathymetric Mapping of Shallow Water Using Aerial Images With Structure-From-Motion Approach: A Case Study Of Kepulauan Seribu Water, Dki Jakarta - Sulistian, Teguh; Gularso, Herjuno; Arum, Dewi Sekar; Aditya, Sandi; Mugiarto, Fajar Triady (Jurnal Geospasial Indonesia, 2024)
Bathymetric mapping is crucial for marine spatial planning and coastal infrastructure development. However, shallow waters with depths ranging from 0 to 5 meters are considered critical areas that pose dangers to conventional survey vessels. This research examines a bathymetric mapping method for the shallow waters of Kepulauan Seribu, Jakarta, using aerial images captured by an unmanned aerial vehicle (UAV) with a structure-from-motion (SfM) approach. Furthermore, the point cloud must be corrected for the refractive index since light passes through both air and water. The seawater refractive index is derived from salinity and seawater temperature data. The validation process uses several independent control points (ICPs) obtained from GNSS real-time kinematic (RTK) measurements and soundings conducted with an unmanned surface vessel (USV). The accuracy assessment shows that the SfM point cloud data has a horizontal RMSE of 0.103 m and a vertical RMSE of 0.191 m. The aerial image approach significantly speeds up the acquisition process compared to conventional sounding methods and produces a higher density of point clouds, integrating the coastal digital elevation model (DEM) of both land and sea areas. However, the use of this method is limited to clear waters where the seabed is visible in the images.